Optimization of Problem-Based Student Performance Assessment in Fiqh Learning - Fajrin, Nadhifa; Sari, Indah (TARBAWY: Indonesian Journal of Islamic Education, 2024)
This study aims to evaluate the implementation of problem-based student performance assessment instruments in Fiqh subjects at MTs YAPI Pakem. Problem-based assessment is designed to improve students’ problem-solving and critical reasoning skills. The research method used is qualitative with a case study approach, where data collection is carried out through documentation, interviews, and observations. The results of the study indicate that the use of problem-based performance assessment instruments can improve students’ thinking skills and encourage active student involvement in the learning process. However, this study also found several obstacles, namely the lack of instructor understanding of the assessment method and time constraints in the learning process. These findings emphasize the importance of training for instructors and adjusting learning time to optimize the implementation of problem-based assessment.